2022
DOI: 10.1136/bmjsem-2021-001240
|View full text |Cite
|
Sign up to set email alerts
|

Return to match running performance after a hamstring injury in elite football: a single-centre retrospective cohort study

Abstract: ObjectivesTo determine the number of matches to return to pre-injury match running performance after sustaining an acute hamstring injury.MethodsIn this retrospective cohort study, the injuries of the players of the first, Under21, Under19, Under18 and Under17 teams of a professional football club in the period 2017–2020 were analysed. Acute hamstring injuries with a minimal absence from training or match play of 7 days were included. For running performance, we assessed the following variables: maximal veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Restoring high‐speed running ability following a hamstring injury represents an important aim for the rehabilitation and return to play process, 8 yet, as part of this process little attention has been paid to the subsequent on‐field performance of professional football players recovered from hamstring injury 10,11 . We have demonstrated that players returning to match‐play after hamstring injury experienced reductions in high‐speed running distances and maximal sprinting speed that are not distinguishable from the within‐subject match‐to‐match variability in the context of the present study.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Restoring high‐speed running ability following a hamstring injury represents an important aim for the rehabilitation and return to play process, 8 yet, as part of this process little attention has been paid to the subsequent on‐field performance of professional football players recovered from hamstring injury 10,11 . We have demonstrated that players returning to match‐play after hamstring injury experienced reductions in high‐speed running distances and maximal sprinting speed that are not distinguishable from the within‐subject match‐to‐match variability in the context of the present study.…”
Section: Discussionmentioning
confidence: 54%
“…10 This study was limited by a relatively small sample that aggregated data from different sports (football, rugby union, and rugby league). A study in a group of 15 footballers from one organization suggested that the majority of players (83%) return to pre-injury maximum match running speed within two games, with maximum running speed taking, at most, five games to return to pre-injury levels 11 and other running metrics (relative total distance covered, relative distance covered at 17.5-22.5 km/h and relative distance covered at >22.5 km/h) normalizing sooner. Aside from this, there are no published data documenting return to sport running performance after hamstring injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation